Ending Extreme Poverty and Sharing Prosperity : Progress and Policies - Cruz, Marcio; Foster, James E.; Quillin, Bryce; Schellekens, Philip (World Bank, Washington, DC, 2016)
With 2015 marking the transition from the Millennium to the Sustainable Development Goals, the international community can celebrate many development successes since 2000. Three key challenges stand out: the depth of remaining poverty, the unevenness in shared prosperity, and the persistent disparities in non-income dimensions of development. First, the policy discourse needs to focus more directly on the poorest among the poor. While pockets of ultra-poverty exist around the world, Sub-Saharan Africa is home to most of the deeply poor. To make depth a more central element in policy formulation, easy-to-communicate measures are needed, and this note attempts a step in this direction with person-equivalent measures of poverty. Second, the eradication of poverty in all of its forms requires steady growth of the incomes of the bottom 40 percent. Yet, economic growth, a key driver of shared prosperity, may not be as buoyant as before the global financial crisis. Third, unequal progress in non-income dimensions of development requires addressing widespread inequality of opportunity, which transmits poverty across generations and erodes the pace and sustainability of progress for the bottom 40. To meet these challenges, three ingredients are core to the policy agenda: sustaining broad-based growth, investing in human development, and insuring the poor and vulnerable against emerging risks.